Pharmacokinetics of Oral and Inhaled Terbutaline after Exercise in Trained Men - Dyreborg, Anders; Krogh, Nanna; Backer, Vibeke; Rzeppa, Sebastian; Hemmersbach, Peter; Hostrup, Morten (Frontiers in Pharmacology, 2016)
Abstract Aim The aim of the study was to investigate pharmacokinetics of terbutaline after oral and inhaled administration in healthy trained male subjects in relation to doping control. Methods Twelve healthy well-trained young men (27 ±2 yrs) (mean ±SE) underwent two pharma-cokinetic trials that compared 10 mg oral terbutaline with 4 mg inhaled terbutaline. During each tri-al, subjects performed 90 min of bike ergometer exercise at 65% of maximal oxygen consumption. Blood (0-4 hours) and urine (0-24 hours) samples were collected before and after administration of terbutaline. Samples were analyzed for concentrations of terbutaline by high performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS). Results Pharmacokinetics differed between the two routes of administration. Serum Cmax and area under the serum concentration-time curve (AUC) were lower after oral administration compared to inhalation (Cmax: 4.2 ±0.3 vs. 8.5 ±0.6 ng/ml, P≤0.001; AUC: 422 ±23 vs. 1308 ±119 ng/ml×min). Urine concentrations (sum of the free drug and the glucuronide) were lower after oral administration compared to inhalation 2 hours (1100 ±213 vs. 61 ±11 ng/ml, P≤0.05) and 4 hours (734 ±116 vs. 340 ±50 ng/ml, P≤0.001) following administration, whereas concentrations were higher for oral ad-ministration than inhalation 12 hours following administration (190 ±43 vs. 399 ±114 ng/ml, P≤0.05). Urine excretion rate was lower after oral administration than inhalation the first 2 hours following administration (P≤0.001). Systemic bioavailability ratio between the two routes of admin-istration was 3.8:1 (inhaled : oral) (P≤0.001). Conclusion Given the higher systemic bioavailability of inhaled terbutaline compared to oral, our results indicate that it is difficult to differentiate allowed inhaled use of terbutaline from prohibited oral ingestion based on urine concentrations in doping control analysis.